2000
DOI: 10.1021/jp0008492
|View full text |Cite
|
Sign up to set email alerts
|

Rearrangement Pathways of Arylperoxy Radicals. I. The Azabenzenes

Abstract: The potential energy surfaces for the reaction of pyridinyl radicals with O 2 have been studied using the B3LYP method. The initial production of the pyridinylperoxy radical followed by either simple decomposition or rearrangement to yield the intermediates (pyridinyloxy, dioxiranylpyridinyl, or dioxetanylpyridinyl radicals) has been explored. Transition-state structures for most of the steps are presented as well as relative free energies over a range of temperatures from 298 to 2000 K. The energetics of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…81 The oxidative decomposition of the aromatic radicals formed by the H-atom abstraction channel of relevance to hightemperature combustion chemistry has been the focus of several recent papers. 16,17,[82][83][84] During the review process, we became aware of a new hybrid HF-DFT method, the MPW1K formalism, which has been shown to improve the calculation of barrier heights for reactions involving smaller systems by a factor of 3 over the B3LYP method. To test if this technique would provide better agreement with experiment than the B3LYP method for the reactions studied in this paper, we employed the MPW1K/6-31+G(d,p) method to calculate the barriers for the radical addition and H-atom abstraction reactions of benzene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…81 The oxidative decomposition of the aromatic radicals formed by the H-atom abstraction channel of relevance to hightemperature combustion chemistry has been the focus of several recent papers. 16,17,[82][83][84] During the review process, we became aware of a new hybrid HF-DFT method, the MPW1K formalism, which has been shown to improve the calculation of barrier heights for reactions involving smaller systems by a factor of 3 over the B3LYP method. To test if this technique would provide better agreement with experiment than the B3LYP method for the reactions studied in this paper, we employed the MPW1K/6-31+G(d,p) method to calculate the barriers for the radical addition and H-atom abstraction reactions of benzene.…”
Section: Discussionmentioning
confidence: 99%
“…The subsequent reaction pathways available following the initial addition of H, O, and OH to aromatic hydrocarbons of relevance to low-temperature atmospheric chemistry are the subject of a study that will be reported in a separate paper ,, …”
Section: Discussionmentioning
confidence: 99%
“…By analogy to the formation of benzene via cyclopentadienyl (C 5 H 5 ) and methyl [30][31][32], both of which are observed in the present work, PhN can be produced through the reaction of C 5 H 5 and CN, as shown in formula (1). Fadden et al pointed out that the phenoxy radical may be formed from the reaction of C 6 H 5 and O 2 [33]. In the same way, PhN can be generated via the addition N 2 to C 6 H 5 .…”
Section: Formation and Destruction Of Phnmentioning
confidence: 99%
“…Laboratory simulation of the formation and reactions of organic molecules in the interstellar medium is a difficult task. On the other hand, during the last three years there is a rapidly growing interest for the use of the quantum chemical ab initio and density functional theory (DFT) methods to study chemical mechanisms and energetics of interstellar organic reactions, mainly in the gas phase. While many researches in the field try to employ the true electron correlation models (for example 11-14a,15-18,23-26 ), the use of the B3LYP hybrid functional becomes more and more frequently reported. ,,,, Besides the interstellar chemistry, this method was used in the studies of many other organic reactions (some of them involving gaseous amino acids and related compounds 51,55,58 ). The reason for this growing popularity can be understood from the reported comparison of B3LYP to much more expensive methods: in many cases the DFT results (geometries and energies) were noted to be in a remarkably good agreement with those obtained by the higher-level theories CISD, CCSD, CASSCF 14a,17,28-31,58 and G2 23,30,59 or demonstrated even the top performance approaching, as the ideal case, to experimental data. 14b-e,,,,,,…”
Section: Introductionmentioning
confidence: 99%